An Improved Technique for Recording the Occurrence of Essential Oil Glands - Cleiy, R. A.; Ross, J. D.
An improved technique is described for producing an actual and permanent record of the number and distribution of essential oil glands on the surface of leaves. A fresh leaf is pressed onto thermal printer paper in order to rupture the oil glands which then leave an image as black dots on the paper. This rapid and inexpensive technique is suitable for both laboratory and field usage.
Keywords: GLANDULAR TRICHOMES; ESSENTIAL OIL GLANDS; GLAND DISTRIBUTION; LABIATAE